Dancing with tears in our eyes: political hipsters, alternative culture and binational urbanism in Israel/Palestine. Issue 6 (3rd May 2021) - Kaddar, Merav; Monterescu, Daniel
ABSTRACT: Excessive redevelopment and gentrification in Jaffa produced liminal extra-territories which serve as fertile grounds for the emergence of unruly urban agencies. Drawing on seven years of ethnographic observations, interviews, and social media analysis of Anna Loulou bar, we outline the contours of a new social type – the political hipster. Unlike the archetypical hipster that could flourish in any urban setting, this specific agent is the product of the particular blend of centre and periphery, characteristic of Jaffa and the Anna Loulou bar in particular. On the seam line between "Palestinian" Jaffa and "Jewish" Tel Aviv, Anna Loulou offers the wild nightlife of the centre, complemented by the rugged authenticity of the binational periphery. The bar serves as a unique intersection between two opposing fields – the cultural and the political. This allows the political hipster to juggle between the fields – commodifying identity and erotizing politics: dancing with tears in her eyes.